Penerapan MOORA Untuk Mendukung Efektifitas Keputusan Manajemen Dalam Penentuan Lokasi SPBU - Afriany, Joli; Sinurat, Lidia Ratna Br; Julianty, Indah; Nainggolan, Efidoren L (STMIK Budi Darma, 2018)
A common refueling station is a place where motor vehicles can get fuel. The Fuel Filling Station is known as SPBU (an abbreviation of the General Fuel Filling Station). MOORA, which is Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) is one of the MADM methods that can perform calculations on the value of attribute criteria that help decision makers to produce the right decision in public fuel (gas station). Decision Support System is a computer-based system aimed at assisting decision making in utilizing certain data and models to solve various unstructured problems.